Is there heavy metal contamination in the soils of two banana-growing areas in Tumbes, Peru? - Pacheco Marchán, Samuel Edmundo (2025)
The mining activity conducted in the upper part of the Tumbes River basin (Peru) has been reported by some authors to be contaminating the Tumbes River water with heavy metals, which is used to irrigate agricultural plots in its basin. However, other water bodies, such as the Cabuyal stream, are reportedly not contamined by mining. This study aimed to determine the influence of the Tumbes River and Cabuyal stream waters on the contamination of banana agricultural soils by mercury, lead, cadmium, chromium, and arsenic in Pampas de Hospital (Pampas), which uses water from the river, and Becerra, which uses water from the stream. A total of 25 agricultural soil samples were analyzed: five background samples and four banana samples from Pampas; and 15 agricultural soil samples, five background samples, and two banana samples from Becerra. The pH was recorded at each sampling point. The samples were analyzed using inductively coupled plasma mass spectrometry (ICP-MS). The average results in mg.kg-1 for agricultural soils were as follows: for Pampas, mercury 0.089, lead 29.7, chromium 24.11, cadmium 1.23, and arsenic 19.96; and for Becerra, mercury 0.063, lead 8.93, cadmium 0.29, chromium 41.03, and arsenic 9.92. These values did not exceed their respective Environmental Quality Standards (EQS). The background samples also did not exceed the EQS. The banana fruits showed undetectable levels of the contaminants. Contrary to expectations, the agricultural soils were not contaminated by the heavy metals and metalloid analyzed.